2007
DOI: 10.1002/uog.3989
|View full text |Cite
|
Sign up to set email alerts
|

Predicting preterm delivery in asymptomatic patients with prior preterm delivery by measurement of cervical length and phosphorylated insulin‐like growth factor‐binding protein‐1

Abstract: K E Y W O R D S:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
0
21
0
16
Order By: Relevance
“…These were conducted with limited sample size. The first such study was conducted in patients who were asymptomatic but at high risk due to previous events by Bittar et al [16], showing improved prediction by sequential combined use of cervical length in mid trimester and phIGFBP-1 detection in early third trimester, predicting 91.7% of early preterm births and 80% of total preterm births. They concluded that two tests are independent, as shown by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These were conducted with limited sample size. The first such study was conducted in patients who were asymptomatic but at high risk due to previous events by Bittar et al [16], showing improved prediction by sequential combined use of cervical length in mid trimester and phIGFBP-1 detection in early third trimester, predicting 91.7% of early preterm births and 80% of total preterm births. They concluded that two tests are independent, as shown by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A importância da medida do comprimento do colo uterino e da pesquisa da phIGFBP-1 para a predição do parto prematuro está bem estabelecida na literatura 4,5,7,[14][15][16] , e sua realização se torna de extrema importância para uma assistên-cia pré-natal de qualidade. Considerando que a alteração da flora vaginal se destaca como um dos fatores desencadeantes do parto prematuro, questões vem surgindo a respeito da influência da infecção genital sobre esses marcadores.…”
Section: Discussionunclassified
“…Os mecanismos responsáveis pelo desencadeamento do trabalho de parto, ainda pouco conhecidos, e a etiologia multifatorial, também muitas vezes desconhecida, dificultam a prevenção primária. Dessa forma, a prevenção secundária ganha destaque na medida em que se propõe a identificar aquelas mulheres de maior risco para o parto prematuro pela utilização de marcadores, físicos e bioquímicos, capazes de predizer tal evento, permitindo intervenção em momento oportuno 3,4 . Dentre esses marcadores, vem ganhando destaque nos últimos anos a medida do comprimento do colo uterino (CC) pela ultrassonografia transvaginal (USTV) e a pesquisa de marcadores bioquímicos, como a proteína-1 fosforilada ligada ao fator de crescimento insulina símile (phIGFBP-1) 5,6 .…”
Section: Introductionunclassified
See 2 more Smart Citations